“O militante negro e a esquerda branca”: imprensa negra, movimento negro e a esquerda no Recife da redemocratização (1985-1994) - Correia, Iyalê Tahyrine Moura (2024)
The current research seeks to analyze the relation between the Unified Black Movement (MNU-PE) and left-wing unions and political parties organizations in Recife based on the newspaper Negritude (periodical of the Unified Black Movement in Pernambuco), during the period of redemocratization of Brazil, specifically between the years 1985 and 1994. I seek to understand the existing dialogues and tensions between these organizations and reflect on how the black press, as a collective mobilizer, described in the beginning of the New Republic the anti-racist struggle and the class conflicts in the period of rising of the struggle for rights in which the new subjects from the so-called "new social movements" (of women, black people, indigenous peoples, trade unions) and political parties put projects of society back into dispute. The study of the black press makes it possible to understand the historical experience of being black in Brazil in a multiplicity of dimensions, from elements referring to a historical conscience to the organizational possibilities of a given time.